Production of arrow head product by using CNC machine - Loo, Jeniffer Yan Si; Leong, Sook San; Penny, Ngu Ai Huong; Lim, Zhi Hong; Ngu, Penny Ai Hong; Rajemi, Mohamad Farizal (2013)
In this research, the production of an Arrow Head product using CNC machine is being discussed thoroughly.This research reveals the turning and milling process of using CNC machine.This information is important to the readers in planning future step in fabricating similar type of product.The information is obtained through phone interview and internet. Thus, this paper precisely reveals the actual processes that involve in manufacturing of an arrow head product and discovers the function of utility of different types of CNC machines. Besides, it can widen readers view by studying more about the production of ARROW-LOK Hybrid